Behind the guns : the history of Battery I, 2nd Regiment, Illinois Light Artillery - Brown, Thaddeus C. S., 1838-1927 (Shawnee classics., 2000)
Much has been written of the infantry and the cavalry during the Civil War, but little attention has been paid the artillery. Through the battles of Chickamauga and Missionary Ridge in 1863 and the Atlanta Campaign of 1864 and with General Sherman's forces on the famous March to the Sea, the acts of a courageous fighting group are vividly recounted in Behind the Guns: The History of Battery I, 2nd Regiment, Illinois Light Artillery. Originally published in 1965 in a limited edition, this regimental history of a light artillery unit was written by three of its soldiers, including.